2015
DOI: 10.1161/atvbaha.114.304674
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Plasma Kynurenines With Risk of Acute Myocardial Infarction in Patients With Stable Angina Pectoris

Abstract: Objective-Enhanced tryptophan degradation, induced by the proinflammatory cytokine interferon-γ, has been related to cardiovascular disease progression and insulin resistance. We assessed downstream tryptophan metabolites of the kynurenine pathway as predictors of acute myocardial infarction in patients with suspected stable angina pectoris. Furthermore, we evaluated potential effect modifications according to diagnoses of pre-diabetes mellitus or diabetes mellitus. Approach and Results-Blood samples were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 39 publications
(37 reference statements)
11
106
0
Order By: Relevance
“…For instance, serum levels of KYN were significantly elevated in diabetes retinopathy patients [31], and excessive dietary TRP induced insulin resistance in pigs in another study [32]. A number of recent studies have demonstrated a strong association between the TRP-KYN pathway and IR, and the dysregulation of the TRP-KYN pathway was considered one of the mechanisms underlying the development of IR [33][34][35][36]. Notably, we found that a significant up-regulation of the metabolites of the TRP-KYN pathway in the serum, liver, and muscle tissues suggests that the abnormality in the TRP-KYN pathway could be a contributing factor to the CKD-induced IR.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, serum levels of KYN were significantly elevated in diabetes retinopathy patients [31], and excessive dietary TRP induced insulin resistance in pigs in another study [32]. A number of recent studies have demonstrated a strong association between the TRP-KYN pathway and IR, and the dysregulation of the TRP-KYN pathway was considered one of the mechanisms underlying the development of IR [33][34][35][36]. Notably, we found that a significant up-regulation of the metabolites of the TRP-KYN pathway in the serum, liver, and muscle tissues suggests that the abnormality in the TRP-KYN pathway could be a contributing factor to the CKD-induced IR.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that TF expression in macrophages within atherosclerotic lesions is linked to the Kyn pathway. Although clinical evidence for a relationship between the Kyn pathway and blood coagulation is scant, Pedersen et al showed that elevated plasma Kyn values or Kyn/Trp ratios predict increased risk of acute myocardial infarction in patients with stable angina pectoris 21. Pawlak et al significantly associated TF, TFPI, and prothrombin fragments 1 + 2 with levels of Kyn pathway metabolites in patients with uremia on dialysis 33.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the cancer concept was also closely related to that of genetics. We found here that the use of the keyword "pathway" highlighted all articles pertaining to cell signalling or gene pathways [20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%